2014
DOI: 10.1089/ten.tec.2013.0225
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Development of a High-Throughput Magneto-Mechanostimulation Device for Cartilage Tissue Engineering

Abstract: To recapitulate the in vivo environment and create neo-organoids that replace lost or damaged tissue requires the engineering of devices, which provide appropriate biophysical cues. To date, bioreactors for cartilage tissue engineering have focused primarily on biomechanical stimulation. There is a significant need for improved devices for articular cartilage tissue engineering capable of simultaneously applying multiple biophysical (electrokinetic and mechanical) stimuli. We have developed a novel high-throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Recent studies have found that magnetic fields affect cells, tissues, and entire organisms, including the formation of the extracellular matrix of hyaline cartilage, proliferation of bovine chondrocytes, and the synthesis of proteoglycan [ 29 , 30 ]. Magnetic field bioreactors are advantageous, because they can meet the requirement of sterile culture conditions by contactless culture [ 31 , 32 ]. Most of them consist of one or a group of permanent magnets that influence the behavior of cells through static or dynamic magnetic field strengths ( Figure 1(d) ).…”
Section: Common Types Of Bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found that magnetic fields affect cells, tissues, and entire organisms, including the formation of the extracellular matrix of hyaline cartilage, proliferation of bovine chondrocytes, and the synthesis of proteoglycan [ 29 , 30 ]. Magnetic field bioreactors are advantageous, because they can meet the requirement of sterile culture conditions by contactless culture [ 31 , 32 ]. Most of them consist of one or a group of permanent magnets that influence the behavior of cells through static or dynamic magnetic field strengths ( Figure 1(d) ).…”
Section: Common Types Of Bioreactorsmentioning
confidence: 99%
“…For example, Brady et al constructed a novel high-throughput magnetomechanical stimulation bioreactor. Validation tests showed that the bioreactor provided a unique platform for researchers to study the combined effects of electrical phenomena and mechanical stimulation [ 32 ]. In another study, however, Dikina et al investigated a variable magnetic field bioreactor composed of permanent magnets that were used for the culture of scaffold-free, high-density hMSC sheets, and the results showed that the bioreactor did not enhance chondrogenesis in the cell-only sheets.…”
Section: Common Types Of Bioreactorsmentioning
confidence: 99%
“…Similarly, Brady et al . () designed and validated a high‐throughput bioreactor platform for the application of multiple magnetic fields and mechanical loading regimens simultaneously in multiple chambers with independent control for engineering functional cartilage tissues. In addition to enabling parametric optimization studies, the multi‐array configuration could also be potentially used for drug and toxicology studies with disease models (Domansky et al , ).…”
Section: Design Considerationsmentioning
confidence: 99%
“…For instance, Pavesi et al (2014) developed a multichambered device with adaptable, independent culture chambers to test various electrical stimulation protocols simultaneously for stem cell differentiation towards myocardial phenotype. Similarly, Brady et al (2014) designed and validated a high-throughput bioreactor platform for the application of multiple magnetic fields and mechanical loading regimens simultaneously in multiple chambers with independent control for engineering functional cartilage tissues. In addition to enabling parametric optimization studies, the multi-array configuration could also be potentially used for drug and toxicology studies with disease models (Domansky et al, 2010).…”
Section: Design Considerationsmentioning
confidence: 99%
“… 9 , 10 , 30–32 However, to display variations in an oxygen-controlled environment, bioreactors within a system have to be operating independently. Whereas the independent operation of parallel running bioreactors is described for mechanical stimuli, 33 no such design is available for oxygen-controlled 3D cell culture.…”
Section: Introductionmentioning
confidence: 99%